Births, Deaths, and New Deal Relief during the Great Depression - Fishback, Price V.; Haines, Michael R.; Kantor, Shawn (The Review of Economics and Statistics, 2007)
The article examines the impact of New Deal relief programs on infant mortality, non-infant mortality, and general fertility rates in major U.S. cities between 1929 and 1940. Effects are estimated using a variety of specifications and techniques for a panel of 114 cities that reported information on relief spending between 1929 and 1940. The significant rise in relief spending during the New Deal contributed to reductions in infant mortality, suicide rates, and some other causes of death, while contributing to increases in the general fertility rate. Similar to Ruhm's (2000) findings for the modern United States, the article finds that many types of death rates were pro-cyclical during the 1930s. Estimates of the relief costs associated with saving a life (adjusted for inflation) are similar to those found in studies of modern social insurance programs.